2010
DOI: 10.1101/lm.1685710
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex: Role in acquisition of overlapping associations and transitive inference

Abstract: “Transitive inference” refers to the ability to judge from memory the relationships between indirectly related items that compose a hierarchically organized series, and this capacity is considered a fundamental feature of relational memory. Here we explored the role of the prefrontal cortex in transitive inference by examining the performance of mice with selective damage to the medial prefrontal cortex. Damage to the infralimbic and prelimbic regions resulted in significant impairment in the acquisition of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
59
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 47 publications
10
59
0
1
Order By: Relevance
“…No other regions showed significant retrieval success effects in either ANOVA or simple effects analysis. These findings highlight the unique role of the PFC in predicting trial-by-trial transfer success at test, but not at encoding, and are consistent with the notion of inferential processing during retrieval (DeVito et al, 2010b;Wendelken and Bunge, 2010).…”
Section: Encoding: Mtl Supports Flexibility Through Integration Acrossupporting
confidence: 68%
See 1 more Smart Citation
“…No other regions showed significant retrieval success effects in either ANOVA or simple effects analysis. These findings highlight the unique role of the PFC in predicting trial-by-trial transfer success at test, but not at encoding, and are consistent with the notion of inferential processing during retrieval (DeVito et al, 2010b;Wendelken and Bunge, 2010).…”
Section: Encoding: Mtl Supports Flexibility Through Integration Acrossupporting
confidence: 68%
“…IFG has been implicated in non-mnemonic relational reasoning where multiple relationships must be considered to infer an unknown relationship (Christoff et al, 2001;Wendelken and Bunge, 2010), suggesting that PFC contributions to flexible AC transfer may be through inferential judgments from premise associations (AB and BC, therefore AC). Animal lesion studies have demonstrated that PFC is essential for transitive inference in rats (DeVito et al, 2010b). However, because lesions to PFC were performed before learning, the exact mechanism by which PFC contributes to flexibility could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence from human (Kesner and Rogers 2004;Blumenfeld and Ranganath 2007) and animal (Hirsch and Crepel 1992;Morris et al 1999;Takita et al 1999; There is converging evidence that links fear memory specificity and generality with information processing in the hippocampus-thalamus-PFC-amygdala circuit (Marr 1971;O'Reilly and McClelland 1994;Leutgeb et al 2007;McHugh et al 2007;Kumaran and McClelland 2012;Nakashiba et al 2012;Xu et al 2012;Navawongse and Eichenbaum 2013;Xu and Sudhof 2013). Involvement of the PFC in context or odor discrimination during information acquisition has been previously studied (DeVito et al 2010;Xu et al 2012;Xu and Sudhof 2013); however, the contribution of the PFC in the discrimination of auditory patterns, such as FM-sweep direction, has not been previously explored. FM-sweep direction discrimination is important in speech recognition (Zeng et al 2005) but its underlying neural mechanism is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of neural substrates and mechanisms underlying memory resolution are focused on the hippocampal circuit (Leutgeb et al 2007;Sahay et al 2011). Recent studies also implicate prefrontal circuitry in the contextual fear memory specificity and generalization (Xu et al 2012;Xu and Sudhof 2013) or discrimination of more discrete multiple odor stimuli (DeVito et al 2010).…”
mentioning
confidence: 99%
“…In rodents, mPFC lesions impair various forms of spatial memory (Lee and Kesner 2003;Jo et al 2007; Lee and Solivan 2008;Churchwell et al 2010). The mPFC has also been shown to be involved in a number of nonspatial memory tasks, including fear conditioning and extinction (Sotres-Bayon and Quirk 2010), transitive inference (DeVito et al 2010), and memory for sequential order (DeVito and Eichenbaum 2011). Although these studies clearly suggest that the mPFC is involved in typical rodent memory tasks, there is currently no consensus about the precise contribution of the PFC to memory encoding and retrieval processes.…”
mentioning
confidence: 99%